Hubungan Verbal Bullying dengan Self-Confidence pada Siswa Sekolah Dasar: Systematic Literature Review - Whenni Injar Setia Rini (CV. ITTC INDONESIA, 2026)
This study is motivated by the prevalence of verbal bullying among elementary school students, which is often perceived as harmless joking behavior by the surrounding environment, despite its potential to negatively affect students’ psychological development, particularly self-confidence. Although various studies have examined the relationship between verbal bullying and self-confidence, the findings remain inconsistent and have not yet been systematically integrated. The aim of this study is to identify the forms of verbal bullying, analyze its impact on self-confidence, and explore the factors influencing variations in its effects among elementary school students. This research employs a qualitative approach using a Systematic Literature Review (SLR) design. The procedure follows the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) framework, consisting of identification, screening, eligibility, and inclusion stages. Literature was collected from Google Scholar using the keywords verbal bullying, self-confidence, and elementary school. From 500 identified articles, 10 studies met the inclusion criteria and were analyzed through synthesis and integration of findings. The results show that the most common forms of verbal bullying include teasing, insults, derogatory nicknames, physical shaming, and inappropriate name-calling related to parents. Verbal bullying generally has a negative impact on students’ self-confidence, which is reflected in feelings of embarrassment, low self-esteem, fear of speaking, social withdrawal, and reduced classroom participation. The variation in its impact is influenced by students’ personal characteristics, coping abilities, family support, peer relationships, and teacher and school responses. Overall, the relationship between verbal bullying and self-confidence is shaped by both psychological and social factors.